2016
DOI: 10.2306/scienceasia1513-1874.2016.42.247
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase inhibition and cytotoxicity of flavonoids and chalcones from Derris indica

Abstract: ABSTRACT:Derris indica, a Thai medicinal plant, contains biologically active substances such as flavone, flavanone, chalcone, and rotenoid compounds. Many compounds from this plant show antitumour, antihyperglycaemic, and anti-inflammatory activities. In this study, eleven compounds including six flavonoid and five chalcone compounds were isolated from the seed of D. indica. Their structures were established on the basis of NMR spectroscopic data. Desmethoxykanugin showed 100% inhibition to acetylcholinesteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…This showed that the benzyl group at C-4 plays a crucial role in the AChE inhibition. Various other natural and synthetic chalcones have been reported as AChE inhibitors [ 44 , 45 , 46 , 47 , 48 ], and chalcones are known to have multiple functions in the treatment of AD, because they inhibit the amyloid beta (Aβ) self-assembly and promotes disassembly of Aβ oligomers [ 49 ]. It has been estimated that the number of AD patients will reach 70 million by 2050, due to a rapidly increasing aging population and the unavailability of drugs to cure this disease [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This showed that the benzyl group at C-4 plays a crucial role in the AChE inhibition. Various other natural and synthetic chalcones have been reported as AChE inhibitors [ 44 , 45 , 46 , 47 , 48 ], and chalcones are known to have multiple functions in the treatment of AD, because they inhibit the amyloid beta (Aβ) self-assembly and promotes disassembly of Aβ oligomers [ 49 ]. It has been estimated that the number of AD patients will reach 70 million by 2050, due to a rapidly increasing aging population and the unavailability of drugs to cure this disease [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The isolation, structural elucidation and percentage yield were reported in a previous study. 10) 2.1. Cell culture.…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxicity of candidone towards HepG2 cells was determined using an MTT assay. 10) The cells were initially added to 96-well plates at a concentration of 1 × 10 5 cells/well, and incubated at 37˚C for 48 h. The cells were then incubated with various concentrations of candidone (1, 10 and 100 µM) for 24 h, using DMSO (dimethyl sulfoxide) as the negative control and 10 µg/ml doxorubicin as the positive control. The culture medium…”
Section: Cell Cytotoxicity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Portanto, a inibição da BACE-1 é um tratamento estratégico promissor para a DA, pois sua inibição resultará na diminuição da produção do peptídeo β-amiloide e nos consequentes sintomas da DA [3] . Chalconas têm sido relatadas como compostos apresentando um amplo perfil de atividade biológica sob a BACE-1 [4] . Com base em estudos in silico verifica-se que chalconas contendo grupos amino interagem com o sítio catalítico da BACE-1 [5] , de modo que poderiam ser potencialmente inibidoras dessas enzimas.…”
Section: Introductionunclassified